2021
DOI: 10.21923/jesd.866532
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaf Polyphenols Loaded Mucoadhesive Oral Films

Abstract: Among drug delivery systems, mouth dissolving films (MDFs) are a form of drug administration with many advantages. Some problems could be experienced, primarily in pediatric and geriatric patients with conventional drug delivery methods as swallowing. It is of great convenience to dispensing the drug with a film dispersed in the mouth in such cases. In this study, for the preparation of films, the solvent casting method was preferred. The effect of biopolymer ratio and loaded olive leaf extract on the film pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a previous study, Köse et al (2021) examined the total phenolic contents and antioxidant capacities of Gemlik‐cultivar olives harvested from Fethiye district of Muğla province. The authors concluded that the ABTS value of green olives was found to range between 403.10 and 502.77 μmol Trolox/100 g.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, Köse et al (2021) examined the total phenolic contents and antioxidant capacities of Gemlik‐cultivar olives harvested from Fethiye district of Muğla province. The authors concluded that the ABTS value of green olives was found to range between 403.10 and 502.77 μmol Trolox/100 g.…”
Section: Resultsmentioning
confidence: 99%
“…The bypass of first-pass metabolism along with direct systemic delivery via transepithelial transport increases therapeutic effectiveness and decreases dosage frequency which is of great interest for patients. This advantage would be a boon to geriatric patients 4 suffering from Parkinson's disease related dysphagia, coma and other age related discomforts.…”
Section: Introductionmentioning
confidence: 99%